2014
DOI: 10.12693/aphyspola.125.a-174
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting from Vibrations of a Two-Degree-of-Freedom Mechanical System

Abstract: In the paper, the energy harvesting from vibration of two-degree-of-freedom mechanical system is analyzed. The considered system consists of two mass linked in series by means of springs and dampers. The kinematic excitation of the system was assumed. The energy conversion system was placed in the suspension of lower mass. As a result of the analysis, the methods to increase the energy harvesting from vibration were proposed. The laboratory stand has been built and a series of measurements performed. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The platform of the vibration exciter was equipped with a magnetostrictive displacement transmitter (10) and an LA30 linear motor (12). The central and upper platforms were equipped with incremental encoders (4,8).…”
Section: Active Noise and Vibration Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The platform of the vibration exciter was equipped with a magnetostrictive displacement transmitter (10) and an LA30 linear motor (12). The central and upper platforms were equipped with incremental encoders (4,8).…”
Section: Active Noise and Vibration Controlmentioning
confidence: 99%
“…7. The control subsystem was used to implement control algorithms for the vibration exciter and active vibration reduction system [8]. The control subsystem consisted of cRIO controller provided with a programmable array of logic gates FPGA, real time processor, and input/output modules.…”
Section: Active Noise and Vibration Controlmentioning
confidence: 99%
“…For example, Balato et al (2017) demonstrated an H-bridge Graetz rectifier with a smoothing capacitor to convert AC current generated in resonant electromagnetic vibration harvester into DC current supplying resistance load. Snamina and Orkisz (2014) proposed an H-bridge Graetz rectifier, enabling the accumulation of energy recovered from vibrations in 2DOF mechanical system in largecapacity capacitors. Grzybek and Micek (2017) described an H-bridge Graetz that was applied in the mechanical system with a self-powered vibration sensor, including piezoelectric material.…”
Section: Introductionmentioning
confidence: 99%